Blucher Physics Proceedings 2018
DOI: 10.5151/ecfa2018-17
|View full text |Cite
|
Sign up to set email alerts
|

Síntese de biodiesel a partir da mistura de óleo de soja:gordura animal e óleo fusel

Abstract: Biodiesel é um biocombustível, obtido através da reação de transesterificação, promissor substituto do diesel de petróleo. Os benefícios de sua utilização é que a combustão deste biocombustível emite menores quantidades de gases poluentes e por ser renovável. A utilização do biodiesel não é amplamente empregada devido ao seu valor comercial ser superior ao do diesel. Uma das formas de tornar o biodiesel economicamente competitivo com o diesel é utilizando matérias-primas de menor valor para transesterificação.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These drops called micelles are formed from bile salts and bile phospholipids along with fatty acids. They are smaller than fats serving as a means of transporting nutrients in the intestine [14,15] In this work, a dynamic-molecular study of such aggregates was carried out, assembling a system very close to that found within our organism. Sodium Cholate (CS), a biological surfactant interacting with oleic acid (AO), saponi ed oleic acid (AOS) and biodiesel (BD) was used.…”
Section: Introductionmentioning
confidence: 99%
“…These drops called micelles are formed from bile salts and bile phospholipids along with fatty acids. They are smaller than fats serving as a means of transporting nutrients in the intestine [14,15] In this work, a dynamic-molecular study of such aggregates was carried out, assembling a system very close to that found within our organism. Sodium Cholate (CS), a biological surfactant interacting with oleic acid (AO), saponi ed oleic acid (AOS) and biodiesel (BD) was used.…”
Section: Introductionmentioning
confidence: 99%